2021
DOI: 10.1101/2021.06.01.21257781
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of obesity in female reproductive conditions: A Mendelian Randomisation study

Abstract: Background: Obesity is observationally associated with altered risk of many female reproductive conditions. These include polycystic ovary syndrome (PCOS), abnormal uterine bleeding, endometriosis, infertility, and pregnancy-related disorders. However, the roles and mechanisms of obesity in the aetiology of reproductive disorders remain unclear. Methods and Findings: We estimated observational and genetically predicted causal associations between obesity, metabolic hormones, and female reproductive condition… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 105 publications
0
3
0
Order By: Relevance
“…Although other anthropometric features like hip-to-waist ratio (WHR) may be better indicators of health for some phenotypes [44], this information is not routinely collected in clinical settings or reported in EHRs. Furthermore, evidence does suggest that clinically ascertained BMI may be more informative for PCOS than WHR [45]. Finally, despite using the largest PCOS GWAS to date for this analysis, our PCOS PRS still only explains a small portion of PCOS genetic variance.…”
Section: Discussionmentioning
confidence: 93%
“…Although other anthropometric features like hip-to-waist ratio (WHR) may be better indicators of health for some phenotypes [44], this information is not routinely collected in clinical settings or reported in EHRs. Furthermore, evidence does suggest that clinically ascertained BMI may be more informative for PCOS than WHR [45]. Finally, despite using the largest PCOS GWAS to date for this analysis, our PCOS PRS still only explains a small portion of PCOS genetic variance.…”
Section: Discussionmentioning
confidence: 93%
“…Here, we observed that increased BMI and metabolic disorder and insulin resistance (IR) were characteristics of infertile women with PCOS, but not UI. PCOS can lead to obesity; on the other hand, the increasing obesity epidemic, with its related metabolic disorders, is associated with an increased risk of many female reproductive conditions (19).…”
Section: Discussionmentioning
confidence: 99%
“…(36) Furthermore there is evidence that increased BMI can lead to conditions associated with decreased fertility. (37) In addition, low adiposity may contribute to reduced fertility as undernutrition may reduce functioning of the reproductive system and lead to defective concentrations of adipocyte-related regulators of endocrine processes such as leptin. (38,39) Previous research has shown a J shaped association between BMI and subfertility, (40) however it is worth noting that our analysis only evaluated linear effects.…”
Section: Potential Mechanismsmentioning
confidence: 99%